2018
DOI: 10.1007/s10784-018-9384-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring national and regional orchestration of non-state action for a < 1.5 °C world

Abstract: The importance of actions by non-state and sub-national actors (e.g., companies and cities) is increasingly recognized, because current governmental commitments are insufficient to limit the increase of global temperatures to 1.5°C. Orchestration, the alignment between 'orchestrator' (e.g., international organizations and governments) and 'intermediaries' (e.g., city networks and partnerships), could harness additional contributions by building catalytic linkages and by enabling a growing number of actions. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 18 publications
0
49
0
Order By: Relevance
“…2 PA "well below" 2 degrees) and secondly the 1.5-degree target. This shows that current efforts are not enough [13,21,23,26,29,75,79].…”
Section: Discussion and Concluding Remarks: The Paris Objective And Cmentioning
confidence: 99%
See 1 more Smart Citation
“…2 PA "well below" 2 degrees) and secondly the 1.5-degree target. This shows that current efforts are not enough [13,21,23,26,29,75,79].…”
Section: Discussion and Concluding Remarks: The Paris Objective And Cmentioning
confidence: 99%
“…Referring to the EU, or Germany, as a good example in terms of climate policies has not even had merit in the past, despite some singular successes [11,56,72,76,78,79]. That the negotiating parties have not reached a better result in Paris bears witness that: In Paris, the EU has pledged minus 40 percent greenhouse gas emissions by 2030 as the (supra-)national climate contribution according to Art.…”
Section: Discussion and Concluding Remarks: The Paris Objective And Cmentioning
confidence: 99%
“…The main assumptions are that all commitments are fully implemented and that the pace of action elsewhere is not impacted. At this moment, we believe the latter is a valid assumption, as there is limited coordination on policy implementation between national governments and other actors (Chan et al, 2018a). Therefore, we did not quantify the coordination effects between national governments and other actors, nor the interaction between policy instruments at different scales.…”
Section: Scenarios Investigatedmentioning
confidence: 99%
“…Our analysis only included actors from 10 high-emitting countries, while in reality sub-national and non-state climate actions take place globally. Studies have shown that the full extent of climate action often goes unreported, particularly among actors from the Global South (Chan et al, 2018a;Chan & Hale, 2015;Hsu et al, 2016;UNFCCC, 2018;Widerberg & Stripple, 2016) and varies across economic, geographic, and national contexts. For businesses, not all companies are willing to make their climate action commitments public.…”
Section: Incomplete Coverage Of Existing Sub-national and Non-state Cmentioning
confidence: 99%
“…)., ; Bulkeley et al, ). This raises the question whether most of their benefits would accrue in the global North rather than where resilience against climate impacts and sustainability needs are most urgent (Chan, Ellinger, & Widerberg, ). Moreover, nonstate actions that aim to intervene in developing countries could effectively address one objective while still leading to negative secondary impacts.…”
Section: The Promise Of Nonstate Actionsmentioning
confidence: 99%